STUDY OF SERUM ADENOSINE DEAMINASE LEVEL IN TYPE 2 DIABETES MELLITUS AND ITS CORRELATION WITH GLYCEMIC CONTROL - D. Hemalatha; Vinod Kumar R P; P. Ravisekar; T. Rajini Samuel (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Diabetes mellitus (DM) is a chronic endocrine metabolic disorder but largely preventable non communicable disease which is responsible for millions of deaths annually, debilitating complications, and incalculable human misery.  Objective: To estimate the level of Serum Adenosine deaminase (ADA) among the patients with type 2 diabetes mellitus through a case control study and to evaluate the correlation of Adenosine deaminase with glycemic control (HbA1C).Methods: The study was conducted in a sample of 60 Type 2 diabetic patients attending diabetic outpatient department and 40 healthy non diabetic individuals who came for routine check -up at Sree Balaji Medical College & Hospital.Results: ADA levels was significantly high in controlled diabetics (group II with HbA1C < 7) and was much higher in Uncontrolled diabetics (group III with HbA1C > 7) compared to healthy controls (group I). Comparison of the parameters (FBS, PPBS, HbA1C, ADA) between the 3 group was done using Student t test and was statistically significant.  Pearson’s coefficient correlation was done between ADA and HbA1C and found a positive correlation between them and had a statistical significance. This indicates that ADA raises with the extent of severity of type 2 diabetes. Positive correlation of ADA with HbA1C provides the information that ADA can be considered to reflect the glycemic status of the individual.Conclusions: Adenosine deaminase (ADA) levels are increased in type 2 diabetics and positive correlation of ADA with glycemic control conveys that ADA may serve as a prognostic factor in type II diabetes mellitus. ADA, being an important enzyme for modulating the bioactivity of insulin and its essential role in the effect of insulin   and glycemic control, it may also serve as a tool in assessing the extent of oxidative stress. All these features of ADA provides evidence to suggest ADA as a glycemic marker of type II diabetes